Revisiting Antibiotic Resistance Spreading in Wastewater Treatment Plants – Bacteriophages as a Much Neglected Potential Transmission Vehicle - Lood, Rolf; Ertürk, Gizem; Mattiasson, Bo (Frontiers in Microbiology, 2017)
The spread of antibiotic resistance is currently a major threat to health that humanity is facing today. Novel multi- and pan-drug resistant bacteria are reported on a yearly basis, while the development of novel antibiotics is lacking. Focus to limit the spread of antibiotic resistance by reducing the usage of antibiotics in health care, veterinary applications, and meat production, have been implemented, limiting the exposure of pathogens to antibiotics, thus lowering the selection of resistant strains. Despite these attempts, the global resistance has increased significantly. A recent area of focus has been to limit the spread of resistance through wastewater treatment plants (WWTPs), serving as huge reservoirs of microbes and resistance genes. While being able to quite efficiently reduce the presence of resistant bacteria entering any of the final products of WWTPs (e.g. effluent water and sludge), the presence of resistance genes in other formats (mobile genetic elements, bacteriophages) have mainly been ignored. Recent data stress the importance of transduction in WWTPs as a mediator of resistance spread. Here we examine the current literature in the role of WWTPs as reservoirs and hotspots of antibiotic resistance with a specific focus on bacteriophages as mediators of genetic exchange.